Taxation and the Allocation of Talent - Lockwood, Benjamin B.; Nathanson, Charles G.; Weyl, E. Glen (Journal of Political Economy, 2017)
Taxation affects the allocation of talented individuals across professions by blunting material incentives and thus magnifying nonpecuniary incentives of pursuing a “calling.” Estimates from the literature suggest that high-paying professions have negative externalities, whereas low-paying professions have positive externalities. A calibrated model therefore prescribes negative marginal tax rates on middle-class incomes and positive rates on the rich. The welfare gains from implementing such a policy are small and are dwarfed by the gains from profession-specific taxes and subsidies. These results depend crucially on externality estimates and labor substitution patterns across professions, both of which are very uncertain given existing empirical evidence.